1948 and the Cold War in Malaya: Samplings of Malay Reactions - Abdul Rahman Haji Ismail, (Kajian Malaysia, 2009)
This paper is a preliminary report of an on-going research on the reactions of the Malays in Malaya to the coming of the Cold War to the region, with particular reference to the importance of the year 1948. For the majority of the Malays, the Cold War was most popularly associated with the Emergency, which British authorities had declared in the effort to quell the armed uprising mounted by the MCP. The vast majority of Malays in Malaya were not interested in the on-going Cold War between the Western bloc led by the United States on the side the Eastern bloc led by the Soviet Union on the other. The preoccupations of the Malays during the immediate post-Pacific War period was nationalism and the concomitant effort to gain independence for Malaya from Britain. Inparticular, they had been rather anxious that the Malays, who were the native of the land, were not robbed of the custodianship over Malaya and political privileges of the Malays in independent Malaya. Consumed with these issues, the Malays had little interests in external affairs. It was perhaps the lack of Malay support that foredoomed the fate of communism in Malaya.